Imagined intergroup contact promotes prosocial behavioral intentions through intergroup anxiety in the United Kingdom and Malaysia - Ma'rof, Aini Azeqa; Zaremohzzabieh, Zeinab; Abdullah, Haslinda (Behavioral Science Research Institute, 2023)
This research study investigates the mediating influence of intergroup anxiety in the linkage between imagined contact and prosocial behavioral intentions. Authors extend the existing literature on imagined contact by incorporating behavioral scripts and a visual perspective as part of the intervention. To further enhance the generalizability of the findings, the study was conducted in two distinct phases, encompassing diverse target groups of 147 British and 251 Malay students enrolled in universities in the United Kingdom and Malaysia, respectively. In the first experiment, the results revealed a significant main effect of condition, indicating high levels of altruistic intention after participants imagined contact (M = 3.82, SD = 0.32), in contrast to the control condition (M = 3.00, SD = 0.32). Additionally, the analysis demonstrated significantly reduced levels of intergroup anxiety (M = 2.06, SD = 0.35) and egoistic intention (M = 1.97, SD = 0.31). The findings also highlighted the mediating role of intergroup anxiety in the relationship between imagining positive contact and all three prosocial behavioral intentions: altruistic intention (β = 0.04, p < .001), egoistic intention (β = -0.02, p < .001), and willingness to donate (β = 0.19, p < .001). In the second experiment, the results were consistent with those obtained in the first experiment. These findings suggest that techniques involving a third-person perspective and the integration of intended behavior in imagery tasks not only enhance positive behavioral outcomes but also mitigate prejudice effectively.